(untitled) (AYUSHDHARA, 2015)
Aim: To access the effect of Pipalli and Shatavari choorna with Shukhoshna godugdha in Stanyakshaya. Objective: Study of literature regarding Stanyakshaya and Pippli choorna. Observation on the effect of Pippali choorna with Godugdha on lactating mother and observe if any adverse effect. Method: Study Group: 60 patients were observed & treated, Study divided in two groups 30 patients in each group. In Group A (Trial Group) 30 patients are randomly selected in which Stanyakshaya will be treated with Pipplichoorna, 500 mg twice daily after meals with Sukhoshana Godugdha. In Group B (Control Group) 30 patients are Group of randomly selected in which Stanya Jananan drug Shatavarimool choorna 2 gm twice daily with Godugdha after meal. A follow up was done on each patient after every 7 days. Initially all the signs and symptoms were noted thoroughly. Change in signs and symptoms in each follow up were observed and noted in case paper. Follow up was done for 3 weeks during treatment and for 2 weeks after treatment. The total duration of treatment was 21 days. Results: Comparing all the symptoms before and after treatment had positive results of treatment given to group B (Shatavari Choorna) showed slightly better results over treatment given to group A (Pippali choorna). The Statistical Analysis reveals that Shatavari Choorna with Shukhoshna godugdha in the management of Stanyakshaya is more effective than Pippalichoorna with Shukhoshna godugdha. Conclusion: Treatment given to group B (Shatavari Choorna) showed better results over treatment given to group A (Pippali choorna), we can conclude that treatment Shatavari Choorna given to group B is better for this disease Stanyakshaya.